Fragmentation, dispersion and segregation urbanization in the rural environment in bragança Paulista/SP (1970 – 2018) - Cerejo, Lucas Nakamura; Bueno, Laura Macho de Mello (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2022)
The urban space as a social construction, allows different readings from the influence of different agents and their territorial impacts, from their social extract and their spatial location. This article present the urbanization process in Bragança Paulista which is located near the metropolitan areas of Sao Paulo and Campinas for the last decades. Through the analysis and mapping the approved land parcels and the ones under analysis by the City Hall, we can ascertain the socio-spatial segregation processes and the way in which they consolidate in the territory. The accelerated urbanization of Bragança is associated to the permissiveness of the urban legislation that corroborated bad practices from the real estate market increasing the urban segregation. Through the analysis of the allotments, we could identify patterns in different parts of the Brazilian territory, from the occupation of rural areas to the south and the compromise of the natural landscape, as well as the designation of the north part of the territory for the lower income and social interest housing, according to the urban legislation associated with the real estate interests.